Association of mitochondrial deoxyribonucleic acid mutation with polymorphism in CYP2E1 gene in oral carcinogenesis - Rahul Pandey; Divya Mehrotra; Carlo Catapano; Vimal Choubey; Rajiv Sarin; Abbas Ali Mahdi; Stuti Singh (Elsevier, 2012)
ABSTRACT: Background: Oral carcinogenesis is a complex process affected by genetic as well as environmental factors. CYP2E1 gene is involved in metabolism of number of compounds and carcinogens. Its normal functioning is required for homeostasis of free radical. Mitochondrial deoxyribonucleic acid (mtDNA) is 10-100 times more susceptible to damage than nuclear DNA. Mitochondrial DNA large scale deletions are well documented in oral cancer. However, the relationship between CYP2E1 gene polymorphisms and mtDNA damage is still not documented in literature. Materials and Methods: Case-control study involving 50 subjects was carried out. Deoxyribonucleic acid extraction was done from study subject tissue samples. Restriction fragment length polymorphism (RFLP) and polymerase chain reaction (PCR) amplification was done to confirm CYP2E1 gene polymorphisms. The PCR amplification was done for mtDNA 4977 bp deletion. Statistical analysis was carried out using SPSS version 11.5 with χ2 tests. Results: c1c1 and DD polymorphisms are prevalent in North Indian population having oral cancer. These polymorphisms are significantly associated with mtDNA 4977 bp deletion. Conclusion: Mitochondrial DNA damage induced by wild CYP2E1 forms and imperfect DNA repair in mtDNA may act synergistically to greatly enhance oral cancer risk.